Health conditions of young and old elderly - Reis, Cibelle Barbosa; Jesus, Rozeli Santos de; Silva, Carla Silvana de Oliveira e; de Pinho, Lucinéia (Rev Rene, 2016)
Objective: to evaluate the elderly about the socio-demographic profile and health conditions in the age groups from 60 to 75 years old (“young” elderly) and above 76 years (“old” elderly). Methods: this is a cross-sectional study and home based. The data were collected applying a questionnaire based on the model developed by the Older Americans Resources and Services. Results: 118 elderly participated in the study, being 68.6% “young”, 58% illiterate, 85.2% with income less than two minimum wages and 70.4% with non-white skin. The “old” elderly had a higher proportion of loss of the companion (p=0.002), non-communicable chronic diseases (p=0.023) and dependence to perform activities of daily living (p=0.036). Both age groups had low physical activity, excessive consumption of medicaments and chewing problems. Conclusion: the model of health facing the elderly, should not be restricted to treatment of diseases but cover their functional capacity.